2019
DOI: 10.3201/eid2501.180111
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antibiotic Cycling Policy on Incidence of Healthcare-Associated MRSA and Clostridioides difficile Infection in Secondary Healthcare Settings

Abstract: This quasi-experimental study investigated the effect of an antibiotic cycling policy based on time-series analysis of epidemiologic data, which identified antimicrobial drugs and time periods for restriction. Cyclical restrictions of amoxicillin/clavulanic acid, piperacillin/tazobactam, and clarithromycin were undertaken over a 2-year period in the intervention hospital. We used segmented regression analysis to compare the effect on the incidence of healthcare-associated Clostridioides difficile infection (HA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 44 publications
1
38
0
1
Order By: Relevance
“…Similar findings were observed in other studies [17,[23][24][25]. This increase is of importance since their use has been linked to the development of resistance in several studies [1,[4][5][6]26]. It is important to note that carbapenems are used mainly in hospitals and as such the observed increase in use would mainly be in hospitalized patients.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Similar findings were observed in other studies [17,[23][24][25]. This increase is of importance since their use has been linked to the development of resistance in several studies [1,[4][5][6]26]. It is important to note that carbapenems are used mainly in hospitals and as such the observed increase in use would mainly be in hospitalized patients.…”
Section: Discussionsupporting
confidence: 83%
“…The overuse and misuse of antimicrobials has increased the risk of emergence and spread of AMR globally [1,2]. Due to the selective pressure imposed by antibiotic agents over bacterial populations, antibiotic consumption has been clearly shown to contribute to the selection and spread of drug resistant microorganisms [3][4][5]. The rapid evolution and development of antibiotic resistance responsible for human infection, and the decrease in the number of new antibiotics approved, critically necessitate conserving the effectiveness of existing antibiotics [1].…”
Section: Introductionmentioning
confidence: 99%
“…Also, there was significant difference in carriage rate of S. aureus among farm workers in different farms. Studies showed different rates of S. aureus in different regions (11,12). Our study showed higher rate compared to a study performed in Mosul-Iraq by Shareef et al, (13), who reported an incidence rate of S. aureus in poultry, ranging from 62.5 to 79.16%.…”
Section: Discussionmentioning
confidence: 99%
“…A 3-year ASP intervention, for example, was associated with increased MRSA incidence. 33 However, a study that analyzed data from 6 postintervention years found a large and significant reductions in MRSA incidence in the last 2 years of the study. 34…”
Section: Sir Decreased After the Mandatementioning
confidence: 99%